The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1055/s-2004-814184
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Magnifying Endoscopy in the Diagnosis of Early Gastric Cancer

Abstract: The minute surface structure and microvessels observed by magnifying endoscopy were related to histopathological findings. Magnifying endoscopy is valuable for predicting the histological nature in the diagnosis of early gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 9 publications
0
76
0
1
Order By: Relevance
“…The fine observation provides information about histological characteristics of the detected lesions. Small regular patterns were observed more frequently in differentiated adenocarcinoma; lack of visible structure and irregular patterns were characteristic to undifferentiated adenocarcinoma (Otsuka et al, 2004). In differentiated carcinoma, the regular SECN pattern disappeared and irregular microvessels proliferated within the cancerous mucosa.…”
Section: High-grade Dysplasia (Hgd) and Early Gastric Cancer (Egc)mentioning
confidence: 90%
“…The fine observation provides information about histological characteristics of the detected lesions. Small regular patterns were observed more frequently in differentiated adenocarcinoma; lack of visible structure and irregular patterns were characteristic to undifferentiated adenocarcinoma (Otsuka et al, 2004). In differentiated carcinoma, the regular SECN pattern disappeared and irregular microvessels proliferated within the cancerous mucosa.…”
Section: High-grade Dysplasia (Hgd) and Early Gastric Cancer (Egc)mentioning
confidence: 90%
“…Therefore, it is often found that the definitive diagnosis of MALT lymphoma can not be obtained after multiple biopsies even in cases where gastric MALT lymphoma is suspected based on endoscopic features of conventional endoscopy. The usefulness of magnified endoscopy (ME) combined with narrow band imaging (NBI) is well recognized in the diagnosis of gastritis and gastric cancer [6][7][8][9] . Recently, the characteristic features of gastric MALT lymphoma, based on magnified endoscopic imaging without NBI, were reported by Ono et al [10] .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first description in the English literature of magnifying endoscopic classification and the characteristic definition of gastric post-ER scar lesions which includes comparative pathology for both magnifying and conventional procedures. Diagnosis of early gastric cancer relies on macroscopic findings by CE, namely flat, elevated, or depressed; color identical to the neighboring noncancerous area, red or pale; the presence of granules or nodules; the presence or absence of ulcers; and the presence or absence of fold conversions, among others [13] . During diagnostic endoscopy, the endoscopist usually takes routine biopsies from even inconspicuous lesions that appear slightly erythematous, discolored, flat, granular, or shallow depressed mucosal areas in the stomach [14,21] .…”
Section: Discussionmentioning
confidence: 99%
“…ME with a narrow band image can aid in deciding the target of endoscopic biopsy for surveillance in Barrett's esophagus [5][6][7][8] . The relationships between ME findings and gastric neoplastic histology, including the types of cancer detected, are now being investigated, and the usefulness of ME for diagnosing early gastric cancer has been reported [9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%